Analysis of Development Potential of Health Resort Enterprises on the Example of Przedsiębiorstwo Uzdrowisko Ciechocinek S.A. in Aleksandrów County - Zajączkowski, Marcin; Cegliński, Paweł (Journal of Education, Health and Sport, 2018)
The purpose of this article is to present the key environmental conditions influencing the management of a health resort enterprise on the example of Przedsiębiorstwo Uzdrowisko Ciechocinek S.A. operating in the Aleksandrów County in the Kujawsko-Pomorskie Voivodeship. The article outlines the profile of the company and presents the most important enironmental factors in the assessment of the authors, based in particular on statistical data. The considerations were based, among others, on the studies of the Central Statistical Office and the Voivodeship Statistical Office in Bydgoszcz. Global trends, which are currently noticeable on the market of tourist services, including health resorts, indicate a strong interest in the sector commonly referred to as "health tourism". This is determined mainly by the fact that the population is aging, the emphasis on prevention, a healthy lifestyle, spa and wellness fashion and increased awareness of health care, also among young people. These issues should form the basis for the creation of a omprehensive offer of spa, medical and tourist services. It is not possible to develop such an offer without raising the standard of facilities, without an increase in the quality and the diversity of services offered and close cooperation of health resort entities with local governments